P2 BSCI/BSTI coronary artery calcification guidelines change management and predict prognosis regardless of age. (21st September 2022) - Graby, John; Soto-Hernaez, Jimena; Murphy, David; Oldman, James LAF; Charters, Pia FP; Burnett, Tim A; Thanaraaj, Thuvaarahan; Barrishi, Adam; Masterman, Benjamin J; Khavandi, Ali; Rodrigues, Jonathan CL
Abstract : Objective: BSCI/BSTI guidelines recommend reporting coronary artery calcification (CAC) on all CTCHEST regardless of indication. This study assessed CAC prevalence, prognosis and potential clinical impact of its reporting in routine CTCHEST. Methods: Single-centre retrospective analysis of consecutive CTCHEST (January-December 2015) for 200 patients per age group (<40, 40–49, 50–59, 60–69, 70–79, 80–89, ≥90). CTs were re-reviewed for CAC presence and severity, excluded if prior coronary intervention. Comorbidities, statin prescription and clinical outcomes (myocardial infarction [MI], stroke and all-cause mortality) were recorded. Impact of reporting CAC was assessed against pre-existing statin indication/prescription. Results: 1344 were included (mean age 63±20 years, 56% female). Inter- and intra-observer variability for CAC presence (ICC 0.95, p<0.001; ICC 1.0, p<0.001) and severity (ICC 0.92, p<0.001; ICC 1.0, p<0.001) was excellent. CAC was observed in 728/1344 (54%), more frequently in males (p<0.001) and rising age (p<0.001). Severity increased with age (p<0.001). A high proportion of patients in all age groups with CAC had no prior statin indication/prescription (42% of 80–89 to 100% of <40). 'Number needed to report' to potentially impact management (all age groups) was 2. 691 (51%) patients died (median follow-up 73 months). CAC presence was associated with risk of MI, stroke and all-cause mortality (p<0.001). After adjusting for confounders, severe calcification predicted risk of all-cause mortality (HR 1.6 [1.1–2.2], p=0.01). Conclusion: Grading of CAC was reproducible, and though prevalence rose with age, prognostic and treatment implications were maintained in all ages. Reporting CAC provides a simple opportunity to risk-stratify patients for cardiovascular risk optimisation.